CURCUMIN PROTECTION AGAINST CADMIUM CHLORIDE-INDUCED BIOCHEMICAL ALTERATIONS IN LUNGS OF SWISS ALBINO MICE - KUMARI, AMRITA; SHARMA, SUMAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of the present study was to investigate the protective effect of curcumin against cadmium chloride (CdCl2)-induced toxicity in lungs of albino mice. Methods: Albino mice were divided into eight groups and five mice were kept in each group. The experiment was carried out for 15 and 45 days. Group 1 mice were kept as control. Group 2 mice were given an oral dose of 1 mg/kg body weight of cadmium chloride on alternate days. Group 3 mice were administered an oral dose of 1 mg/kg body weight of cadmium chloride on alternate days and 100 mg/kg body weight of curcumin daily. Group 4 mice were received an oral dose of 100 mg/kg body weight of curcumin daily. Autopsies were done on 15 and 45 days post-treatment. Results: The results of the present study showed a significant decrease in organ weight at both the intervals. Biochemical analysis showed decline in total glycogen, cholesterol, and protein concentration in lung of cadmium chloride-treated mice. Furthermore, the cadmium chloride concentration in cadmium chloride-treated group was increased in comparison to the control group. However, the treatment with curcumin ameliorated cadmium chloride-induced changes in lung tissue as it instigated the antioxidant enzymes remarkably. However, cotreatment of cadmium chloride with curcumin boosted the changes due to cadmium chloride. Conclusion: Hence, we concluded that curcumin has protective efficacy in the lungs against the cadmium chloride generated toxicity in albino mice.